Constraints Faced by Farmers in Adoption of Organic Plant Protection Practices - Aparna, K V; Thomas, Allan (Journal of Extension Education, 2017)
The study was conducted in Thiruvananthapuram district of Kerala with a view to identify the constraints faced by farmers during adoption of organic plant protection practices in vegetables. The three major constraints faced by farmers were crops being affected by drought, lack of proper and timely extension services for transfer of organic technologies and organic produce fetching non-remunerative price. The major suggestions for refinement were regular and frequent farm visits, diagnostic and consultancy by Krishi Bhavan officials and mechanisms to ensure premium price for products derived through organic practices.